2013
DOI: 10.1002/rrq.61
|View full text |Cite
|
Sign up to set email alerts
|

Critical Discourse Analysis in Literacy Education: A Review of the Literature

Abstract: A B S T R A C TThis article is a critical, integrative literature review of scholarship in literacy studies from 2004 to 2012 that draws on critical discourse analysis ( CDA ). We discuss key issues, trends, and criticisms in the field. Our methodology was carried out in three stages. First, we searched educational databases to locate literacy-focused CDA scholarship. Second, we completed an analytic review template for each article and encoded this data into a digital spreadsheet to assess macrotrends in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 106 publications
(183 reference statements)
0
28
0
1
Order By: Relevance
“…They found that the participants in the reviewed studies mostly struggled against dominant ideologies, and many articles called for social action, both on microlevel and macrolevel. The researchers maintain this finding reject the understanding of CDA that it has no plan for constructive alternatives and social action [8].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…They found that the participants in the reviewed studies mostly struggled against dominant ideologies, and many articles called for social action, both on microlevel and macrolevel. The researchers maintain this finding reject the understanding of CDA that it has no plan for constructive alternatives and social action [8].…”
Section: Introductionmentioning
confidence: 89%
“…Rogers & Shaenen focused on the use of CDA method when making a critical, integrative review of literacy education. They found the CDA method used in 76 literacy-focused studies, including curricular design [8]. They reflect on three decades of CDA in literacy studies.…”
Section: Introductionmentioning
confidence: 99%
“…Journals tend to publish literature reviews in specific domains of research approaching a topic in different ways. Rogers and Schaenen (2014), for example, shed light on CDA studies in literacy education in a broad range of journals. Kleinsasser's (2013) review makes a synthesis of research published in one particular journal on the topics of language teachers, language teacher education, teaching and learning.…”
Section: Research Approachmentioning
confidence: 99%
“…Le contenu et la structure des données ont été analysées thématiquement à partir des grands ensembles qui se sont dégagés des entretiens et faisaient bien souvent échos aux recherches sur la mixité scolaire : 1) les savoirs disciplinaires (la grammaire, la littérature, l'éducation physique et sportive, l'histoire, l'éducation à la sexualité et l'éducation civique), 2) le cadre scolaire (la récréation, la gestion des interactions verbales, le placement dans la classe et la question des insultes), puis 3) un domaine transversal plus composite au sein duquel figuraient des questions liées à la forme scolaire et à la légitimité, pour l'école laïque et obligatoire, d'aborder en son sein des questions ne faisant pas consensus. La méthode d'analyse retenue s'inscrit dans les cadres de l'analyse critique de discours définis par Rogers (2011) et Rogers et ses collaboratrices (Rogers, Malancharuvil-Berkes, Mosley, Hui et Joseph, 2005 ;Rogers et Schaenen, 2013).…”
Section: Méthode D'analyse Des Donnéesunclassified